AI and Finance: A Study of Stakeholder Perceptions on Operational and Experiential Evolution - Zaffer, Ziyan; Thadathil, Tessy; Sarika, Wagh (Integrated Journal for Research in Arts and Humanities, 2025)
This study explores the transformative impact of artificial intelligence (AI) on the financial sector. The paper aims to understand the perception about AI-driven technologies in reshaping financial operations, decision-making, and customer experiences in the finance arena. The study uses quantitative methodology. The primary data is collected through a structured survey and data is analysed. The respondents belong the age group of 18 to 60 years. The sample consists of data collected from153 respondents. The secondary data for the study is referred from journal and books on AI and Finance. The research utilizes descriptive analysis to examine the perceptions. The data analysis revealed a mixed level of familiarity with AI among the student fraternity. The discussion underscored that while AI was perceived to offer benefits like enhanced predictive analytics, personalized financial services, and operational efficiency, there would be notable challenges. A significant proportion of respondents expressed concern over cybersecurity risks, disruption of job markets and a lack of familiarity with AI-related regulations in India. Moreover, the analysis shows that AI has yet to gain widespread usage in financial services, indicating both untapped potential and a need for increased public education on AI applications in finance. The study concludes by emphasizing the importance of ethical frameworks and collaborative industry efforts to ensure that AI integration in finance benefits consumers and strengthens financial stability.